PENGABDIAN MASYARAKAT MELALUI GERAKAN GEMAR MENABUNG, REBRANDING UMKM, DAN PENYULUHAN PENIPUAN DIGITAL DI DESA KEDUNG PENGAWAS KECAMATAN BABELAN KABUPATEN BEKASI - Salman Hafidzul Haq; Agus Dharmanto, Dhema Kayla Rezyva Hermawan, Bayuputra Widyadhana Askar, Delfina Ambar Auralita, Dia (JOURNAL OF COMMUNITY DEDICATION, 2026)
Community service through the Student Community Service Program (KKN) is a form of higher education contribution to help communities address various social issues in their local environment. The KKN program of Group 42 in Kedung Pengawas Village, Babelan District, Bekasi Regency, was implemented to respond to community needs in three main areas: children’s financial literacy, strengthening micro-enterprise identity, and improving community digital literacy. This topic was chosen because children still had limited understanding of financial management from an early age, micro-enterprise actors faced constraints in building their business image, and cases of digital fraud that harmed the community were increasing. The implementation methods included field observation, community needs identification, and a participatory approach through the “Gerakan Gemar Menabung” program for elementary school students, UMKM rebranding assistance through banner creation, and digital scam prevention education for residents. The results showed an increase in children’s understanding of the importance of saving, improved visual appeal and business identity for UMKM, and greater community awareness of online fraud schemes. This activity demonstrates that KKN programs designed according to community needs can provide tangible benefits in supporting.